2011
DOI: 10.1021/am200371c
|View full text |Cite
|
Sign up to set email alerts
|

Honeycomb-Structured Films by Multifunctional Amphiphilic Biodegradable Copolymers: Surface Morphology Control and Biomedical Application as Scaffolds for Cell Growth

Abstract: Recently, fabrication of functional porous polymer films with patterned surface structures at the scale from nanometer to micrometer has been attracting increasing interests in material science and nanobiotechnology. In this work, we present new preparation of two series of multifunctional amphiphilic copolymers and preparation of their microporous thin films on solid substrates. First, diblock dendritic poly(l-lysine)-b-poly(l-lactide)s and triblock dendritic poly(l-lysine)-b-poly(l-lactide)-b-dendritic poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 68 publications
2
50
0
Order By: Relevance
“…Furthermore, since P3 possesses too much PDMAEMA, some droplets are still forced to coalesce, thus interconnected pores and irregular surface are formed. It has been reported that molecular hydrophilicity can affect the pore size and regularity of honeycomb fi lms in earlier studies; [ 6,12,14 ] however, to the best of our knowledge, it is the fi rst time that molecular hydrophilicity has been found to play a crucial role in the porous layers of honeycomb fi lms.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…Furthermore, since P3 possesses too much PDMAEMA, some droplets are still forced to coalesce, thus interconnected pores and irregular surface are formed. It has been reported that molecular hydrophilicity can affect the pore size and regularity of honeycomb fi lms in earlier studies; [ 6,12,14 ] however, to the best of our knowledge, it is the fi rst time that molecular hydrophilicity has been found to play a crucial role in the porous layers of honeycomb fi lms.…”
mentioning
confidence: 87%
“…[ 11,12 ] For instance, superhydrophobic property is highly desirable when honeycomb fi lms are employed as hydrophobic and lipophobic materials such as self-cleaning surface, [ 8 ] whereas applications in the fi eld of biology, such as cell-based biosensor technologies, microfl uidic cell screening systems, tissue engineering, call for well-ordered hexagonal porous arrays with hydrophilic character since the interaction between surface and cells can be enhanced by the increased hydrophilicity. [ 1,13,14 ] Accordingly, if the surface wettability of honeycomb fi lms can be reversibly changed by external stimuli, the fi lms will have much wider applications, ranging from hydrophilic to hydrophobic areas. Furthermore, simply employing triggers to regulate surface wettability of honeycomb fi lms will replace cumbersome work Adv.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 40 ] By controlling these variables, the quality, pore size, pore size distribution, and pattern regularity can be fi nely tuned and optimized. The mean pore size usually shows a monotonic correlation with concentration [ 71,72 ] and humidity. [ 73,74 ] At the same time, the regularity of the pattern will also be affected.…”
Section: Infl Uence Of C a And Rh On The Surface Morphologymentioning
confidence: 99%